A PEGDA/DNA Hybrid Hydrogel for Cell-Free Protein Synthesis - Cui, Jinhui; Wu, Dan; Sun, Qian; Yang, Xiuzhu; Wang, Dandan; Zhuang, Miao; Zhang, Yiheng; Gan, Mingzhe; Luo, Dan (Frontiers in Chemistry, 2020)
Cell-free protein synthesis (CFPS) has the advantage of rapid expression of proteins and has been widely implemented in synthetic biology and protein engineering. However, the critical problem limiting CFPS industrial application is its relatively high cost, which partly attributes to the over expense of the single-used DNA templates. Hydrogels provide a possible solution because it can preserve and reutilize the DNA templates in CFPS and has great potential in elevating protein production yield of CFPS. Here, we presented a low-cost hybrid hydrogel simply prepared with polyethylene glycol diacrylate (PEGDA) and DNA, which is capable of high-efficient and repeated protein synthesis in CFPS. Parameters governing protein production specific to hybrid hydrogels were optimized. Structures and physical properties of the hybrid hydrogel were characterized. Transcription and expression kinetics of solution phase system and gel phased systems were investigated. The results showed that PEGDA/DNA hydrogel can enhance protein expression of CFPS system and enable a repeated protein production for tens of times. This PEGDA/DNA hybrid hydrogel can serve as recyclable gene carrier for either batch or continuous protein expression, and pave a path toward more powerful, scalable protein production and cell-free synthetic biology.